Acceptability and perceived feasibility of the KaziKidz health promotion intervention among educators and caregivers in schools from South Africa: a qualitative descriptive study - Patricia Arnaiz; Manfred Max Bergman; Harald Seelig; Larissa Adams; Danielle Dolley; Markus Gerber; Nandi Joubert; Siphesihle Nqweniso; Peter Steinmann; Jürg Utzinger; Rosa du Randt; Cheryl Walter; et al. (BMC, 2024)
Abstract Background Despite the uncontested benefits of physical activity, its promotion lags behind in the public health agenda of low- and middle-income countries (LMICs). School-based interventions are promising strategies to foster health during childhood, but evidence of their effectiveness is limited and inconclusive for LMICs. Thus, further investigation is needed on contextual factors associated with intervention implementation in low-resource settings. We studied the acceptability and feasibility of the KaziKidz health promotion intervention and its implementation and make recommendations to improve future adoption and sustainability. Methods KaziKidz was implemented in four primary schools from low-income communities in South Africa in 2019. Semi-structured interviews with four school principals, three focus group interviews with 16 educators, and another three with 16 caregivers were conducted between October and November 2021. Participants were purposively recruited. Interview transcripts were analyzed via thematic analysis using a deductive and reflexive approach. Results Three main themes influencing intervention implementation and adoption were identified: (1) prioritizing teachers' needs (2), integrating the program into the school structure, and (3) creating opportunities in the community. Supporting recommendations included: (theme 1) adopting intervention approaches that are inclusive of educators' health and providing them with capacity development and external support; (theme 2) fostering a feeling of ownership and belonging among school stakeholders to adapt interventions to specific resources and needs; and (theme 3) raising community awareness to encourage individuals to claim power over and actively engage with the program. Conclusions Comprehensive interventions comprising health support, adequate training, and ongoing assistance for educators combined with school-wide and community outreach actions seeking to strengthen program ownership, accountability, and engagement can enhance uptake of school-based interventions and long-term maintenance. Trial registration ISRCTN15648510, registered on 17/04/2020.